An analysis of police interview discourse and its role(s) in the judicial process - Haworth, Kate (2009)
This study analyses the current role of police-suspect interview discourse in the England & Wales criminal justice system, with a focus on its use as evidence. A central premise is that the interview should be viewed not as an isolated and self-contained discursive event, but as one link in a chain of events which together constitute the criminal justice process. It examines: (1) the format changes undergone by interview data after the interview has taken place, and (2) how the other links in the chain – both before and after the interview – affect the interview-room interaction itself. It thus examines the police interview as a multi-format, multi-purpose and multi-audience mode of discourse.